Nicotine induces morphological and functional changes in astrocytes via nicotinic receptor activity. Issue 8 (14th April 2021) - Aryal, Surya P.; Fu, Xu; Sandin, Joree N.; Neupane, Khaga R.; Lakes, Jourdan E.; Grady, Martha E.; Richards, Christopher I.
Abstract: Nicotine is a highly addictive compound present in tobacco, which causes the release of dopamine in different regions of the brain. Recent studies have shown that astrocytes express nicotinic acetylcholine receptors (nAChRs) and mediate calcium signaling. In this study, we examine the morphological and functional adaptations of astrocytes due to nicotine exposure. Utilizing a combination of fluorescence and atomic force microscopy, we show that nicotine‐treated astrocytes exhibit time‐dependent remodeling in the number and length of both proximal and fine processes. Blocking nAChR activity with an antagonist completely abolishes nicotine's influence on astrocyte morphology indicating that nicotine's action is mediated by these receptors. Functional studies show that 24‐hr nicotine treatment induces higher levels of calcium activity in both the cell soma and the processes with a more substantial change observed in the processes. Nicotine does not induce reactive astrocytosis even at high concentrations (10 μM) as determined by cytokine release and glial fibrillary acidic protein expression. We designed tissue clearing experiments to test whether morphological changes occur in vivo using astrocyte specific Aldh1l1‐tdTomato knock in mice. We find that nicotine induces a change in the volume of astrocytes in the prefrontal cortex, CA1 of the hippocampus, and the substantia nigra. These results indicate that nicotine directly alters the functional and morphological properties of astrocytes potentially contributing to the underlying mechanism of nicotine abuse. MAIN POINTS: Nicotine induces time‐dependent remodeling in astrocytic processes via nicotinic acetylcholine receptors activity. Long‐term nicotine exposure increases Ca 2+ activity but does not cause reactive astrocytosis. Nicotine increases the volume of astrocytes i​n vivo. ​